A new species of the genus Duolandrevus (Orthoptera: Gryllidae: Landrevinae) from China - Ma, Libin; Gorochov, Andrej V.; Zhang, Yalin (Zootaxa, 2015)
A bark cricket genus Duolandrevus Kirby, 1906 is discussed here. These species are brownish with depressed bodies, with reduced elytra, lack hind wings and live in the bark of dead trees or branches. Duolandrevus are distributed from the south of China and Japan to the Philippines, the Malay Archipelago and New Guinea. Only one species, Duolandrevus hongkongae Otte, 1988, was recorded in China. Here, one additional species, Duolandrevus (Eulandrevus) unguiculatus sp. nov. is described from Southern China. Its description and illustrations and the key to the subgenera of Duolandrevus worldwide are given.